Pragmatic discourse of the comments on Facebook in the Kazakh language - Lyazzat Akhmetkaliyeva, Maira Malik, Dina Alkebaeva, Aizhan Shormakova, Daniyar Kozhan, (Opción, 2019)
The article aims to consider the most frequent linguistic and non-linguistic discourse pragmatic uses of „subjective hybrid texts‟ of the majority of individuals via comparative qualitative research methods. As a result, the peculiarity of the comments in the Kazakh language is in the specificity of the national language, and in the use of traditional stereotypes of the language picture of the world of the national cognitive worldview. In conclusion, considering the pragmatics of the comments of the Facebook users in the Kazakh linguistics, studying them in anthropocentric terms, and revealing their linguistic nature enables us to understand its pragmatic specificity.